2015
DOI: 10.1103/physrevb.91.195412
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast self-action of surface-plasmon polaritons at an air/metal interface

Abstract: We investigate both theoreticaally and experimentally the nonlinear propagation of surface plasmon polaritons (SPP) on a single air/metal interface. Inspired by nonlinear dielectric waveguide theory, we analytically derive a model that describes the nonlinear propagation of SPPs, thus bridging the description of plasmonic and dielectric waveguides. The model, the numerical simulations and the experiments, which are carried out in the hundred femtosecond regime, reveal that the SPP undergoes strong ultrafast se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Ultrafast plasmonic Kerr nonlinearity can substantially influence the propagation of the SPP modes at the metal/dielectric interface, particularly in the case of dielectrics lacking a strong nonlinear response . For example, it was shown both theoretically and experimentally that in this case SPPs experience prominent self‐induced absorption . Nonlinearity may lead to completely unexpected behaviour of SPPs.…”
Section: Nonlinear Surface Plasmon Polaritonsmentioning
confidence: 99%
“…Ultrafast plasmonic Kerr nonlinearity can substantially influence the propagation of the SPP modes at the metal/dielectric interface, particularly in the case of dielectrics lacking a strong nonlinear response . For example, it was shown both theoretically and experimentally that in this case SPPs experience prominent self‐induced absorption . Nonlinearity may lead to completely unexpected behaviour of SPPs.…”
Section: Nonlinear Surface Plasmon Polaritonsmentioning
confidence: 99%
“…Also, the real and imaginary components of the third-order susceptibility of thin gold layers were characterized using the z-scan method [6,7]. In another recent experiment Baron et al [8] measured the imaginary component of the third-order susceptibility for bulk gold by studying nonlinear propagation of surface-plasmon polaritons at a single air/metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…A review by the same authors [102] found that measured values of χ (3) of gold can vary by several orders of magnitude, depending on wavelength, pulse duration, or the nature of the nonlinear experiment. Most strikingly, similar measurements of the nonlinear absorption of SPPs at gold/air interfaces [169] resulted in χ (3) values which were three orders of magnitude larger. In this case, the authors excited SPPs on a gold film using asymmetric gratings, which also collected the light, as shown in Fig.…”
Section: Surface Plasmon Polaritonsmentioning
confidence: 81%